Plurality, Tokyo & Taipei - Noah (da0, 2023)
Plurality is a concept proposed by Audrey Tang, Glen Weyl, and the RadicalxChange community. The concept emphasizes the use of technology to promote collaboration and diversity across social and cultural differences.